Integration Between the Sharia Maqasid Principles and the Sustainable Development Goals (SDGs) - Muslim Marpaung; Irma Suryani Lubis (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
The integration of Maqasid Sharia principles with the Sustainable Development Goals (SDGs) has significant strategic potential for promoting holistic sustainable development, particularly within the context of Islamic banking. Sharia banks operate not merely to achieve economic profitability but also prioritize social welfare and environmental protection, aligning closely with the universal objectives of the SDGs. The core values of Maqasid Sharia—protection of religion, life, reason, offspring, and property—complement several key SDGs, including poverty alleviation, education enhancement, health improvement, and economic equity. This study explores how Sharia banks, exemplified by institutions, utilize various Islamic financial instruments such as zakat, waqf, and sukuk waqf to address socio-economic challenges and support the halal industry, which emphasizes sustainable consumption and production. Despite these efforts, challenges persist, primarily related to low Sharia financial literacy, limiting community engagement with sustainability programs. Thus, increased financial literacy through ethical education aligned with Maqasid Sharia is recommended for optimizing the contribution of Sharia banks towards achieving comprehensive SDGs.